The Influence of Self-efficacy and Learning Motivation on the Numeracy Literacy Ability of Junior High School Students - Julianti, Angelina; Annurwanda, Pradipta; Ellissi, Wike (JPMI (Jurnal Pendidikan Matematika Indonesia), 2025)
This numeracy literacy ability is important in mathematics learning. Self-efficacy and motivation to learn play an important role in improving students' numeracy literacy skills. The purpose of the study was to determine the influence between self-efficacy and learning motivation on numeracy literacy skills in SMP Negeri 2 Ngabang. This study uses a quantitative research method. This research was carried out at SMP Negeri 2 Ngabang with 9 classes totaling 247 students who were the subjects of the research. Then, the sampling technique uses the stratisfied clustur random sampling technique. Data collection includes self-efficacy variables and learning motivation variables by providing questionnaires and test questions for numeracy literacy skills, from the value of these questionnaires and tests is the basis for determining the influence of self-efficacy and learning motivation on students' numeracy literacy skills The test results show that the data is distributed in a homogeneous, normal, and linear manner. Based on data analysis and research findings, it is shown that self-efficacy and learning motivation have a positive and significant influence on the numeracy literacy ability of SMP Negeri 2 Ngabang students. The F test showed a simultaneous effect, with a sig value. 0.000 is less than 0.05. The determination coefficient showed that self-efficacy and learning motivation had the ability of 33.6% to explain the variance in students' numeracy literacy ability and 66.4% was influenced by other independent variables that were not studied in this study.Pengaruh Self-efficacy dan Motivasi Belajar Terhadap Kemampuan Literasi Numerasi Siswa SMP ABSTRAKKemampuan literasi numerasi ini adalah hal yang penting dalam pembelajaran matematika. Self-efficacy dan motivasi belajar memainkan peran penting dalam meningkatkan kemampuan literasi numerasi siswa. Tujuan penelitian adalah untuk mengetahui pengaruh antara self-efficacy dan motivasi belajar terhadap kemampuan literasi numerasi di SMP Negeri 2 Ngabang. Penelitian ini menggunakan metode penelitian kuantitatif. Penelitian ini dilaksanakan di SMP Negeri 2 Ngabang dengan 9 kelas yang berjumlah 247 siswa yang menjadi subjek penelitian. Kemudian, teknik pengambilan sampel menggunakan teknik stratisfied clustur random sampling. Pengumpulan data mencakup variabel self-efficacy dan variabel motivasi belajar dengan cara memberikan kuesioner dan soal tes untuk kemampuan literasi numerasi, dari nilai kuesioner dan tes inilah yang menjadi dasar untuk mengetahui pengaruh self-efficacy dan motivasi belajar kemampuan literasi numerasi siswa Hasil uji menunjukkan data berdistribusi secara homogen, normal, dan linier. Berdasarkan analisisi data dan temuan penelitian menunjukkan bahwa self-efficacy dan motivasi belajar memberikan pengaruh yang positif dan signifikan terhadap kemampuan literasi numerasi siswa SMP Negeri 2 Ngabang. Uji F menunjukkan pengaruh simultan, dengan nilai sig. 0,000 kurang dari 0,05. Koefisien determinasi menunjukkan bahwa self-efficacy dan motivasi belajar mempunyai kemampuan sebesar 33,6% dalam menjelaskan varians terhadap kemampuan literasi numerasi siswa dan 66,4% dipengaruhi variabel independen lain yang tidak diteliti dalam penelitian ini. Kata Kunci :kemampuan literasi numerasi; motivasi belajar; self-efficacy